Persepsi Masyarakat Kecamatan Penjaringan terhadap Kebijakan Pengelolaan Waduk Pluit - Yosia BSMS Silalahi; Iin Ichwandi; Sambas Basuni (Jurnal Manajemen dan Organisasi, 2021)
Pluit Reservoir has a big role in DKI Jakarta. Efforts to optimize the Pluit Reservoir are facing various problems, such as silting the reservoir, water quality pollution, the existence of illegal settlements of the population, thus decreasing the function of the Pluit Reservoir as flood control and water resources. In an effort to overcome the problem, the government has made normalization of reservoir policy. Information regarding the level of knowledge / perception, attitudes and level of satisfaction of the community and management is important to consider the management of the Pluit Reservoir. The purpose of this study is to analyze the level of knowledge / perceptions of the community and managers on the functions, problems and management policies of the Pluit Reservoir, to analyze the attitudes of the community and managers towards the Pluit Reservoir management policy, to analyze the level of community and manager satisfaction with the Pluit Reservoir management policy. The analysis method is descriptive quantitative and qualitative methods using a Likert scale and supply-demand analysis. The results showed that the level of knowledge / perception of both managers and the community was still low on the program of land acquisition and relocation of flats, reservoir dredging programs, and waste cleaning and handling programs. The attitude of both the manager and the community is still low towards the land acquisition and relocation program to flats. The level of satisfaction that is still low both from managers and the community regarding land acquisition and relocation to flats and also with the reservoir dredging program.